O empoderamento feminino e a violência patrimonial no casamento e na união estável - Molina, Viviane (2023)
Women's property rights violations can happen in different ways. Generally, it consists of retaining, subtracting, or destroying objects, withholding assets and resources during the relationship or in the couple separation and sharing, affecting women's livelihood, rights and dignity. In turn, female empowerment reflects the construction of collective consciousness and actions supporting women's rights, acquired through achievements and society's advances. The purpose of this master thesis is to analyze how initiatives within the scope of social, political and legal empowerment, such as projects for the creation of collective consciousness and legal changes, can offer subsidies so that women do not suffer patrimonial violence in the stable and conjugal union. This qualitative research used the deductive method, through bibliographic and documental research on the subject.